The patterns of brain control and its relation to critical thinking in mathematics among fifth scientific branch grade female students (Journal of the College of Basic Education, 2025)
The aim of the research was to find out the patterns of brain control among fifth grade scientific students and the relationship between them and their critical thinking in mathematics, and the researchers used the descriptive method to suit the nature of the research objectives and questions. To verify this, the researchers prepared a test to measure critical thinking, consisting of (60) paragraphs in its final form. The Diane Connell scale was used for cerebral control. The test and the scale were applied to the basic research sample of (260) fifth grade scientific students in Baghdad city schools after conducting statistical analysis of the test paragraphs using the SPSS statistical analysis program. The research results showed that the pattern of brain control prevailing among fifth grade scientific students is the left pattern by 38.1%, followed by the integrated pattern by 36.2% and the right pattern in the last order by 25.7% as well as the results reached that the level of critical thinking in mathematics reached 45.2% while the level of critical thinking skills as follows: Prediction of assumptions 44.8%, evaluation of discussions 46.5%, conclusion 44.5%, deduction 45.1% as the results showed that there are significant differences due to the pattern of brain control of the average scores of the two skills of predicting assumptions and fulfilling discussions from critical thinking skills only. While the results showed that there were significant differences for the overall score of the test attributed to the pattern of cerebral control, that is, there is a relationship between critical thinking and patterns of cerebral control.